IODINE STATUS IN SCHOOL CHILDREN AND DISTRIBUTION OF IODINE, MERCURY, LEAD IN SOIL AND WATER IN THE ENDEMIC GOITER HILL AREA, PONOROGO - Muhamad Arif Musoddaq; Taufiq Hidayat; Khimayah Khimayah (Balai Penelitian dan Pengembangan Kesehatan Magelang, 2021)
Background. Iodine deficiency disorders (IDD) remained a public health problem. Ponorogo was an IDD endemic area with prominent cases of mental retardation. Despite the lack of iodine intake, exposure to environmental heavy metals can exacerbate the effects of iodine deficiency. Objective. To describe iodine status of school children and distribution of environmental iodine and heavy metals including mercury (Hg), lead (Pb), and cadmium (Cd) in the endemic IDD hill area of Ponorogo. Method. This research is a cross-sectional study conducted in two villages in IDD endemic areas in Ponorogo, namely Dayakan and Watubonang villages, in 2011. A total of 127 urine samples of primary-school-age children were taken and analyzed for urinary iodine excretion (UIE). A total of 29 soil samples and 87 water samples were taken from the study site to measure the concentration of iodine and heavy metals Hg, Pb, and Cd. Types of water source, altitude, and land use, both soil and water source were recorded. Results. The median (min-max) UIE was 130 (14 –1187 µg/L) within the range of adequate population iodine intake according to WHO (100-199 µg/L), while the percentage of UIE <100 µg/L was still around 33.07 percent. The concentration of iodine in the soil was 33.777 mg/kg (6.640 –108.809), and the concentration of iodine in the water was 8.0 µg/L (0-49). The concentration of Hg in the soil was 68.64 ppb (7.43–562.05), and the concentration of Hg in the water was 0.00 ppb (0.00-23.24). The concentration of Pb in the soil was 3.273 ppm (0.000–25.227), while Pb was not identified in the water. The Cadmium was not detectable both in the soil and water. Conclusion. Iodine deficiency is still a public health problem in Dayakan and Watubonang villages. The environment of the endemic IDD area in Ponorogo was not completely poor in iodine, but iodine was not evenly spread and mobilized. There was a risk of environmental heavy metal exposure from Hg in the soil or water and Pb in the soil. Mercury in the environment can cause health problems due to the inhibition of the use of iodine in the thyroid gland.